The Impact of Marijuana Legalization on Law Enforcement in States Surrounding Colorado. (June 2019) - Ward, Kyle C.; Lucas, Paul A.; Murphy, Alexandra
Since the legalization of recreational marijuana occurred in Colorado, politicians, academics, and the public have been paying close attention to what impact, if any, the legalization of recreational marijuana has on crime, substance use and abuse, and state revenue gains. However, research has not identified the potential impact that marijuana legalization has had on law enforcement officers in neighboring states. This study used survey methodology to explore how the legalization of recreational marijuana in Colorado has affected law enforcement officers and their duties in states that border Colorado. Using multistage cluster sampling, municipal police departments and sheriff's offices in Kansas, Nebraska, and Wyoming were selected for inclusion in this study based off their proximity to Colorado and because none had legalized either medical or recreational marijuana at the time of this study. Results indicate that law enforcement officers view Colorado's legalization of recreational marijuana as having a negative impact on their enforcement duties. Respondents note an increase in potency, perceived juvenile use, and strain on their resources as major issues they are now having to deal with. Analysis indicates that departments further away from Colorado perceive less of an impact than counties closer to Colorado's border. Compared with Nebraska and Kansas, respondents from Wyoming perceived a larger impact on enforcement, but these differences were diminished when controlling for personal perceptions of marijuana.